We can write this in math as x+y+z=104, x=y-6, and z=3y
Because we already know what x and z are in terms of y, we can substitute our values for x and z into the first equation. This now looks like (y-6) + y + (3y) = 104. Now we can simplify our equation to find our value for y.
y-6 + y + 3y = 104 simplifies to 5y - 6 = 104, then 5y=110, and finally y=22.
Now that we know our value for y we can find our values for x and z by substituting our value for y into the other two equations.
The second equation x = y-6 can be simplified as x = 22 - 6 and further simplified as x = 16.
The third equation z = 3y can be written as z = 3(22) or z = 66.
Our three numbers are 16, 22, and 66. Hope this helps you!
A. Taking out a new car loan
Answer:
P = 20000×1.625^(n/4)
Step-by-step explanation:
An exponential equation can be written using the given data:
value = (initial value)×(growth factor in period)^(n/(period))
Here, the growth is by a factor of 32500/20000 = 1.625, and the period is 4 years. Then your exponential equation is ...
P = 20000×1.625^(n/4)
17,064. Do multipcation and line numbers up, remember to carry.